Growth-Promoting Endophytic Fungus (Stemphylium lycopersici) Ameliorates Salt Stress Tolerance in Maize by Balancing Ionic and Metabolic Status - Ali, Raid; Gul, Humaira; Rauf, Mamoona; Arif, Muhammad; Hamayun, Muhammad; Husna,; Khilji, Sheza Ayaz; Ud-Din, Aziz; Sajid, Zahoor Ahmad; Lee, In-Jung (Frontiers in Plant Science, 2022)
Climate change is a major cause of the world's food security problems and soil salinity is a severe hazard for a variety of crops. The exploitation of endophytic fungi that are known to have a positive association with plant roots, is preferred for improving plant growth, yield, and overall performance under salt stress. The current study thus rationalized to address how salt stress affected the growth, biochemical properties, antioxidant capacity, endogenous IAA, and ionic status of maize associated with endophytic fungus (Stemphylium lycopersici). According to the findings, salt stress reduced chlorophyll a and b, total chlorophyll, total protein, sugars, lipids, and endogenous IAA levels. Enhanced values of chlorophyll a/b ratio, carotenoids, secondary metabolites (phenol, flavonoids, tannins), antioxidant enzyme activity (catalase, ascorbate peroxidase), proline, and lipid peroxidation were noticed in maize plants. under salt stress. Increased ionic content of Na+, Cl-, Na+/K+, and Na+/Ca2+ ratio, as well as decreased Ca2+, K+, Mg2+, N, and P contents, were also found in salt-stressed maize plants. In comparison to the non-saline medium, endophytic association promoted the antioxidant enzyme activities (798.7 Units/g protein; catalase activity, 106 Units/g protein; ascorbate peroxidase activity), IAA content (3.47 mg/g FW), and phenolics and flavonoids (88 and 1.68 µg/g FW, respectively), and decreased MDA content (0.016 nmol/g FW), Na+ ion content (18 mg/g dry weight ), Cl- ion (16.6 mg/g dry weight), Na+/K+ (0.78) and Na+/Ca2+ (1.79) ratios, in maize plants under salt stress. While Ca2+, K+, Mg2+, N, and P contents were increased in maize plants associated with S. lycopersici under salt stress. Current research exposed the role of S. lycopersici as an effective natural salt stress reducer and maize growth promoter, hence it can be used as a biofertilizer to ameliorate salt stress tolerance in crops along with better growth performance in saline regions.